The Separation Characteristics of a High Efficiency Cyclone Separator - MENG Kehan; LU Yiping; DAI Jinglu; ZHANG Songsong (Journal of Harbin University of Science and Technology)
In order to study the separation performance and influencing factors of cyclone separator involved in the atmospheric monitoring system, the structure size of the particle was designed and the threedimensional physical model of the flow field was established by the design criterion of the cyclone separator. Reynolds stress model (RSM) was used to simulate gas velocity field, then the particles phase was added and the gassolid twophase flow was calculated by the discrete phase model. The effect of internal and external vortices on particle motion and the separation of particles is obtained. In order to satisfy the requirements of separation performance, the parameters such as the length and diameter of exhaust pipe were changed successively and the geometric standard deviation of the efficiency curve of separation was calculated and compared on the basis of the initial structure scheme. The result show that the optimal exhaust pipe length is 42mm and diameter is 18mm. It can effectively inhibit the generation of short circuit flow, increase the external vortex area, guarantee the geometric standard deviation is 1.5±0.1, improve the separation efficiency.